PENGAKUAN ASSET TETAP TERHADAP NILAI BUKU ASSET BERSIH STUDIO LOVINDA - Putra, Yosep eka; Yusri, Misbah; Hamdani, Muchlas; Hakim, Muhammad Irfanul; Fikri, Nurul; Ismail, Taufik; Rahmi, Mega (Sekolah Tinggi Ilmu Ekonomi Yasa Anggana Garut, 2025)
Studio Photo Lovinda is a business engaged in photography services located in Cubadak and Kubu Rajo, Lima Kaum District, Tanah Datar Regency, West Sumatra. This study aims to determine whether the recognition of fixed assets, depreciation, and determination of the net book value of assets at Studio Photo Lovinda are in accordance with the Fixed Asset Financial Accounting Standards. The data analysis method used is qualitative descriptive analysis, which is a method that describes the company's condition based on actual conditions in the field. Through this approach, the researcher assesses how Studio Photo Lovinda records the acquisition of fixed assets, determines the useful life, calculates depreciation expense, and determines the book value of assets from year to year. In this final report, the author will analyze the calculation of acquisition cost, depreciation of fixed assets, and disposal of fixed assets and their presentation in Studio Photo Lovinda's financial statements using SAK EMKM as a benchmark. Based on the results of the analysis, Studio Photo Lovinda should record the acquisition of fixed assets, determine the useful life, calculate depreciation expenses, and determine the book value of assets from year to year in accordance with the applicable Financial Accounting Standards, so that the profit presented in the financial statements can reflect the actual value and provide reliable information for decision making.